2009
DOI: 10.1104/pp.108.133165
|View full text |Cite
|
Sign up to set email alerts
|

Cell Culture-Induced Gradual and Frequent Epigenetic Reprogramming of Invertedly Repeated Tobacco Transgene Epialleles  

Abstract: Using a two-component transgene system involving two epiallelic variants of the invertedly repeated transgenes in locus 1 (Lo1) and a homologous single-copy transgene locus 2 (Lo2), we have studied the stability of the methylation patterns and trans-silencing interactions in cell culture and regenerated tobacco (Nicotiana tabacum) plants. The posttranscriptionally silenced (PTGS) epiallele of the Lo1 trans-silences and trans-methylates the target Lo2 in a hybrid (Lo1/Lo2 line), while its transcriptionally sile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 49 publications
3
43
1
Order By: Relevance
“…In a previous study, attenuated expression of cell culture-derived epialleles of an invertedly repeated transgene in tobacco was attributed to methylation mosaicism at the cellular level (Krizova et al 2009). Our study, however, provides evidence that such intermediate expression might also be due to mosaic methylation patterns of individual gene copies.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, attenuated expression of cell culture-derived epialleles of an invertedly repeated transgene in tobacco was attributed to methylation mosaicism at the cellular level (Krizova et al 2009). Our study, however, provides evidence that such intermediate expression might also be due to mosaic methylation patterns of individual gene copies.…”
Section: Discussionmentioning
confidence: 99%
“…Euchromatin, in which active genes reside, was hypermethylated in culture, but only a small percentage of genes obtained heterochromatic marks, which might lead to long-term silencing. Krizova et al (2009) studied the fate of an epigenetically silenced LO1 transgenic allele in tobacco taken through cell culture and regeneration from callus. They observed partial loss of Lo1E 35S promoter methylation compared with leaf tissue in the parent plant.…”
Section: Detection Of Epigenetic Statusmentioning
confidence: 99%
“…Mistargeted de novo methylation would allow the establishment and perpetuation of DNA hypermethylation of promoters, which would create epialleles, and hypomethylation of repetitive DNA, which may lead to activation of mobile elements. Krizova et al (2009) examined the development of a tobacco cell culture into callus followed by plant regeneration. They observed the loss of parental imprinting in 25% of the regenerated tobacco plants, regardless of whether the epiallele was originally methylated or unmethylated.…”
Section: Detection Of Epigenetic Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…However, nuclear runon transcription analysis revealed that the gus as well as OSM and hph genes were subjected to TGS. An IR locus, locus1 in tobacco, epigenetically switched from PTGS to TGS upon prolonged vegetative propagation in tissue culture (Fojtova et al 2003;Krizova et al 2009). The P35S promoter of the TGS silenced nptII gene was hypermethylated.…”
Section: Resultsmentioning
confidence: 99%